DEPRESSION AND CHRONIC PAIN PROBLEM PSYCHOSOMATIC INTERRELATIONSHIP AND THE NEED FOR A COMPLEX APPROACH (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
Depression and chronic pain problem: psychosomatic interrelationship and the need for a comprehensive approach This article examines the complex two-way relationship between depression and chronic pain. Modern studies show that 30-50% of patients with chronic pain suffer from depressive disorders, while depressed patients experience pain more intensely and respond less to treatment. The article analyzes the neurophysiological mechanisms, in particular, the disruption of the serotonin and noradrenaline systems in both conditions, and the involvement of common brain structures in the processing of pain and emotional information. Understanding this connection is important in clinical practice, since a purely medical or purely psychological approach is often ineffective.